Epidermal Growth Factor Induces the Expression of Its Receptor Gene in Human Gastric Carcinoma Cell Line TMK‐1 - Yoshida, Kazuhiro (Jpn J Cancer Res, 1989)
To ascertain the possible autocrine pathway in the growth promotion of gastric carcinomas, a study was made on the effects of exogenous human epidermal growth factor (hEGF) on the expression of mRNA for EGF, transforming growth factor‐α (TGF‐α), EGF receptor, FOS and MYC genes by TMK‐1 cells. Exogenous hEGF increased FOS and MYC mRNA levels 30 min and 1 h after the treatment, respectively. TMK‐1 cells accumulated the mRNA for EGF receptor about 7‐ to 8‐fold by 3 h after treatment Expressions of mRNA for EGF and TGF‐α genes were detected, but the amounts of the mRNA of these genes in TMK‐1 cells were not altered after the treatment.